(untitled) - Novak, Ladislav (Doprava a spoje, 2012)
Natural and social environment is more exposed to emergencies and crisis phenomena. Overlapping of these effects still cause dramatic impacts on nature, civilization, the products and the man himself. These effects are display to the transport processes and transport infrastructure. Slovak Republic responds to these facts by taking action at various levels of public administration. Measures are taken at the legal environment, institutional environment, preparing forces, resources and means to deal with emergencies and crisis situations. Decisive measures are being prepared for economic mobilization and critical transport infrastructures.